Carbon pricing and planetary boundaries - Gustav Engström (Nature Portfolio, 2020)
In the light of nine Earth System Processes (ESPs) and the corresponding planetary boundaries, here the authors assessed the global environmental impact of a global carbon pricing in a multi-boundary world. They show that a global carbon tax would relieve pressure on most ESPs and it is therefore stronger in a multi-boundary world than when considering climate change in isolation.